Eliminating customer experience pain points in complex customer journeys through smart service solutions - Heiko F. Holz; Marc Becker; Markus Blut; Stefanie Paluch (Psychology & Marketing, 2023)
Scholarly understanding of customer journeys has evolved from a linear, single service provider perspective to encompass complex service delivery networks that involve multiple touchpoints governed by various service providers. This intricate setting often gives rise to experiential pain points for customers. To investigate this phenomenon within the context of airport services, our research employs critical incident and problem-centered interviews as well as an analysis of 7192 online airport reviews. In Studies 1a and 2a, we explore the crucial pain points that travelers encounter throughout their airport journey. Complementing these insights, Studies 1b and 2b assess the impact of the identified pain points on travelers' emotions. Building upon a classification of pain points into information, performance, and hospitality themes, Study 3 further examines how smart service solutions, as new technologies, can address and resolve these pain points, ultimately enhancing the customer experience (CX). By accomplishing these objectives, our work contributes a comprehensive classification scheme for experiential pain points in complex customer journeys to the academic discourse on customer journeys. Furthermore, it establishes a connection to the emerging field of research on the impact of smart service solutions on the CX.
Keywords: 650; artificial intelligence; customer experience; customer journey; experiential pain points; service experience; smart service solutions